PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUTY PADA PT. SEPATU BATA TBK PERIODE 2013-2023 - Doni Putra; Rizka Wahyuni Amelia (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Current Ratio and Debt to Equity Ratio on Return On Equity at PT Sepatu Bata Tbk. The research method used is quantitative descriptive method with testing using SPSS version 25 and hypothesis testing. The sample used in this study is the financial statements of PT Sepatu Bata Tbk for the period 2013-2023. The results of this study indicate that partially Current Ratio has no effect and is not significant to Return On Equity obtained tcount 0.438 < t table 2.26216 with a significant value of 0.673 > 0.05. While partially Debt to Equity Ratio has an effect and is significant to Return On Equity, with the results obtained thitung |-6,090|> ttabel 2,26216 with a significant value of 0.000 <0.05. Simultaneously the variables Current Ratio and Debt to Equity Ratio have an effect on Return On Equity, with the results obtained Fhitung 35.669> Ftabel 4.46 with a significance of 0.000 <0.05 and the independent variables consisting of Current Ratio and Debt to Equity Ratio contribute 87,4% to Return On Equity, while the remaining 12,6% is influenced by other factors not explained in this study.